PROTECTION OF CHILDREN’S PERSONAL DATA IN THE DIGITAL WORLD BASED ON NATIONAL AND INTERNATIONAL LEGAL FRAMEWORK - Bismo Jiwo Agung (Lampung Journal of International Law, 2019)
The crime of children’s data in the digital world is one of the causes of the rampant crime of bullying, fraud, theft, sexual harassment, exploitation and abduction which leads to the trafficking of people who make children victims. The method used in this paper is a juridical-normative comparative legal research method. The result shows that the Convention on the Rights of Child Convention 1989 (CORC) does not regulate the personal data in the digital world comprehensively. So far, countries in the world, including Indonesia, have only relied on the international legal framework. It is recommended, including international guidelines issued by several international organizations such as the Organization for Economic Co-operation and Development (OECD), Asia Pacific Economic Cooperation (APEC), and the International Telecommunication Union regarding the guidelines for parents and children in 2016. Indonesia already has a set of legal rules that are used as a basis for protecting children’s rights in the digital world. Based on these rules, the protection of children’s data in the digital world is included in the private and criminal domain. These Legal Frameworks show that the government is passive in protecting children’s data in the digital world because the responsibility of child safety and security when online is still focused on the parents or guardians of the child.